Avaliação de primatas da espécie Callithris Jacchus submetidos ao cativeiro - Ferraz, Myrna Campos [UNESP] (2013)
The classical and instrumental conditioning using positive reinforcement applied to animals Callithrix jacchus were made with practicality and success. In this study the concentrations of salivary IgA in primate species Callithrix jacchus were very low. Since this species used as a model biological studies and being important in the immunoglobulin A and immune status check as an indicator to measure the stress in many animals including non-human primates suggest further studies using other techniques to quantify IgA in the saliva these animals. Possibly due to structural conditions and the lack of past animal, could not complete validation for physiological fecal glucocorticoid metabolites in the species under study. Thus to obtain reliable results in studies using these animals as an experimental model, it is necessary to have a structure against cold and heat, as well as keep the animals protected site visitors, sounds and other animals. Furthermore, there is a need to know the history of animals and the use of a known strain with cohesive colony. The commercial kits from Cayman Chemical ® for detection of progesterone and estradiol in human plasma used in this study for the determination of fecal metabolites of progesterone and estradiol Callithrix jacchus were validated both as laboratory physiologically allowing thereby detect increases or decreases in the concentration of progesterone during the cyclic ovarian activity during pregnancy and also as detecting increases and decreases in the concentration of estradiol in the periods before, during and after pregnancy. The management of the supply of raw propolis Callithrix jacchus aided in weight gain of males and females before the gestational period besides having collaborated in maintaining weight during pregnancy treated group of females, thus suggesting a better feed conversion. Because of the difference in the behavior of animals in days when no stressful events occurred and due to...